(untitled) (International Current Pharmaceutical Journal, 2017)
Pretreatment with oral contraceptive pills (OCP) has been widely applied in IVF/ICSI –ET treatment. However, it remains unclear whether OCP influences pregnancy rate of fresh cycle and subsequent cumulative pregnancy rate in patients with endometriosis. In this retrospective study, a total of 512 first attempt IVF/ICSI cycles of patients with endometriosis were included and divided into two groups: the study group included 216 cycles of patients undergoing pretreatment with OCP before pituitary suppression and ovarian stimulation, while 296 cycles of patients without pretreatment were considered as control. The ovarian stimulation performance and pregnancy results were compared between the two groups. Patients with OCP pretreatment required shorter duration, a lower dosage of gonadotropins, but obtained higher E2 level and more retrieved oocytes. Patients in the two groups obtained comparable fertilization rate, cleavage rate, but the number and rate of day 3 high-quality embryos were higher in OCP-pretreated patients. No differences were found in IVF/ICSI-ET outcomes, in terms of implantation rate, clinical pregnancy rates, live birth pregnancy rate, and cumulative pregnancy rate. In addition, despite the lack of statistical significance, a trend toward higher clinical pregnancy rate in a fresh cycle and cumulative pregnancy rate was found in OCP pretreated patients. It should be recommended that patients with endometriosis take OCP pretreatment before ovarian stimulation, since it offers advantages of lower cost and higher embryo-quality, and does not negatively influence pregnancy rates. Chakrabartty et al., International Current Pharmaceutical Journal, July 2017, 6(8): 44-48 http://www.icpjonline.com/documents/Vol6Issue8/01.pdf